Дослідження селитебних ландшафтів для оптимізації районного планування Волині та потреб сталого розвитку регіону - Тарасюк, Н. А.; Ничая, О. О.; Tarasiuk, N. A.; Nychaia, O. O. (Східноєвропейський національний університет ім. Лесі Українки, 2015)
Розглядається роль селитебних ландшафтів у формуванні сталого розвитку Волинської області, оптимізації районного планування. Виокремлено основні заходи для забезпечення сталого розвитку регіону. It is investigated the role of the inhabited landscapes in the sphere of the forming of the constant development of Volyn’ region and the optimization of the regional planning. It was selected the main points for the providing of the constant development of the region.
The Investigation of the Inhabited Landscapes for the Optimization of the District Planning of Volyn’ and for the Conditions of the Constant Development of the Region
Keywords: селитебний ландшафт; сталий розвиток; функціональні типи селитебних ландшафтів; the inhabited landscapes; constant development; functional kinds of the inhabited landscapes